Linking Budgetary Participation to Budgetary Slack: An Indonesia Perspective - ., Devie; Suralim, Giovanna; Tarigan, Josua; Elsye Hatane, Saarce (International Journal of Engineering and Technology, 2018)
This study examines how budget participation influences budget slack creation propensity through the mediation of distributive and procedural fairness, managerial trust, and budget goal commitment. The data was collected from 103 respondents holding managerial position in 49 Indonesian distribution companies. Despite its limitations, this study has both academic and practical implications. The study adds to the budgetary slack literature in an Indonesian country which has not been widely researched. The result suggests that budget participation influences distributive and procedural fairness, which interact with one another and influence managerial trust. Managerial trust and procedural fairness together influence budget goal commitment, which decreases propensity of budget slack creation. The findings presented in this study should have important implications for Indonesia companies to reduce slack creation and enhance commitment and trust, it is suggested to improve procedural fairness, one of which by implementing budget participation.Â